The Rapid Methylation of T-DNAs Upon Agrobacterium Inoculation in Plant Leaves - Philips, Joshua G.; Dudley, Kevin J.; Waterhouse, Peter M.; Hellens, Roger P. (Frontiers in Plant Science, 2019)
Agrobacterium tumefaciens has been foundational in the development of transgenic plants for both agricultural biotechnology and plant molecular research. However, the transformation efficiency and level of transgene expression obtained for any given construct can be highly variable. These inefficiencies often require screening of many lines to find one with consistent and heritable transgene expression. Transcriptional gene silencing is known to affect transgene expression, and is associated with DNA methylation, especially of cytosines in symmetric CG and CHG contexts. While the specificity, heritability and silencing-associated effects of DNA methylation of transgene sequences have been analysed in many stably transformed plants, the methylation status of transgene sequences in the T-DNA during the transformation process has not been well studied. Here we used agro-infiltration of the eGFP reporter gene in Nicotiana benthamiana leaves driven by either an AtEF1α-A4 or a CaMV-35S promoter to study early T-DNA methylation patterns of these promoter sequences. The T-DNA was examined by amplicon sequencing following sodium bisulfite treatment using three different sequencing platforms: Sanger sequencing, Ion Torrent PGM, and the Illumina MiSeq. DNA methylation was detectable in each promoter region just 2-3 days post infiltration and the levels continued to rapidly accumulate over the first week, then steadily up to 21 days later. Cytosines in an asymmetric context (CHH) were the most heavily and rapidly methylated. This suggests that early T-DNA methylation may be important in determining the epigenetic and transcriptional fate of integrated transgenes. The Illumina MiSeq platform was the most sensitive and robust way of detecting and following the methylation profiles of the promoters in the T-DNA. The utility of the methods was then used to show a subtle but significant difference in promoter methylation during intron-mediated enhancement. In addition, the method was able to detect an increase in promoter methylation when the eGFP reporter gene was targeted by siRNAs generated by co-infiltration of a hairpin RNAi construct.